AN ANALYSIS OF THE ACTIVITIES IN ENGLISH TEXTBOOK (2017 REVISE EDITION) OF 11” GRADE SENIOR HIGH SCHOOL ENTITLED “STOP BULLYING NOW” PUBLISHED BY KEMENDIKBUD - Pakpahan, Sapta Friyanti; Purba, Indah Dewi Sartika; Pakpahan, Srilasima; Saragih, Erikson (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research was conducted to evaluate the english textbookcontent of 11th grade Senior high school (2017 Revise Edition) Entitled